2017
DOI: 10.5222/buchd.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Weight Perception in Adolescents and Their Relationships with Quality of Life and Self-Efficacy

Abstract: ÖZAmaç: Bu çalışmada, ergenlerin vücut ağırlığı (VA) ile ilişkili beden algısının belirlenmesi, beden algısı ile yaşam kalitesi ve özyeterlilik arasındaki ilişkinin saptanması amaçlanmıştır. Yöntem: Çalışma, ortalama yaşları 16,3±1,1 olan 779 (%55,3'ü kız, %44,7'si erkek) ergen ile yapılmıştır. Hesaplanan vücut kitle indeksinin (VKİ) yaş ve cinsiyet persentiline göre değerlen-dirilmesi ile ergenler çok zayıf, zayıf, normal, kilolu ve şişman olarak tanımlanmıştır. Ergenin vücut ağırlığına ilişkin beden algısı s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In studies conducted in our country, it was found that 34.3% of adolescents (Çetinkaya et al, 2017), 35% of adolescents (Hisar & Toruner, 2013), 45.1% of adolescents (Taş et al, 2017), 41.5% of girls and 23.7% of boys (Önal et al, 2019) had body weight misperceptions. A previous study on adolescents aged 15–24 showed a misperception rate of 37.2% about weight status (The Ministry of Health Body weight perception survey in Turkey, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In studies conducted in our country, it was found that 34.3% of adolescents (Çetinkaya et al, 2017), 35% of adolescents (Hisar & Toruner, 2013), 45.1% of adolescents (Taş et al, 2017), 41.5% of girls and 23.7% of boys (Önal et al, 2019) had body weight misperceptions. A previous study on adolescents aged 15–24 showed a misperception rate of 37.2% about weight status (The Ministry of Health Body weight perception survey in Turkey, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…A previous study on adolescents aged 15–24 showed a misperception rate of 37.2% about weight status (The Ministry of Health Body weight perception survey in Turkey, 2012). When we examined these studies, the perception of body weight of adolescents was determined by asking how they perceived themselves verbally/how they perceived their own body (Çetinkaya et al, 2017; Taş et al, 2017) or how low or high they felt from healthy weight (Hisar & Toruner, 2013). Although the results are similar to our study, they report a slightly lower rate body weight misperception than our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ile Çetinkaya ve ark.nın yapmış oldukları çalışmalarda, beden algısının sağlık davranışları üzerinde etkili olduğu saptanmıştır. 6,23 Çalışmamızda benzer biçimde kız öğrencilerinin BKİ değerleri %78,1'inin normal, %12,5'inin zayıf, %8,7'sinin fazla kilolu olduğu saptanmıştır (Tablo 1). Vücut ağırlıklarını tanımlama durumu ile SAÖ kesinlik alt boyutu arasında istatistiksel açıdan fark anlamlı bulunmuştur (p=0,03; p<0,05).…”
Section: Discussionunclassified